Implementation of Business Continuity Planning Methodology in Making Business Continuity Planning Documents at PT. XYZ - Fikri, Ahmad Maulana; Fachrureza, Faisal; Octaraisya, Nadine; Agustyana, Nur Amalia; Putra, M. Gilvy Langgawan; Amalia, Dwi Nur (JBTI : Jurnal Bisnis : Teori dan Implementasi, 2021)
PT. XYZ is a company engaged in the communication sector. As a company with a national scale, PT. XYZ has various risks that must be faced, ranging from natural disasters, human disturbances, and disruption due to technology. The existence of disruption risks can disrupt the company's operational activities. A business continuity plan document is created to find out what steps the company must take to minimize damage due to disruption. Making a business continuity plan or BCP starts from the project initiation stage, risk assessment, business impact analysis, mitigation strategy development, plan development, training, testing, auditing. The results obtained from this research are in the form of BCP documents used by PT. XYZ in response to a disturbance. With the BCP, PT. XYZ can respond to a disruption that occurs and quickly restore business operations.